"A phony way to show sincerity, as we all well know": tobacco industry lobbying against tobacco control in Hong Kong. (24th November 2004) - Knight, J; Chapman, S
Abstract : Objective: To examine the tobacco industry's efforts to influence public policy and block the legislative process on tobacco control in Hong Kong, 1973 to 1997. Method: Systematic review of relevant tobacco industry documents made public via the Master Settlement Agreement. Results: The tobacco industry in Hong Kong has sought to manipulate the policymaking process and delay the introduction of tobacco control legislation in Hong Kong from at least 1973. The industry ensured that each of the government's initial meagre steps toward tobacco control were delayed and thwarted by drawn out "cooperation" followed by voluntary concessions on issues the industry regarded as minor. By the 1980s the government had became increasingly active in tobacco control and introduced a number of initiatives, resulting in some of the tightest legislative restrictions on smoking in Asia. The tobacco industry was successful in thwarting only one of these initiatives. Conclusions: Throughout the 1980s and 1990s two factors played a significant role in hindering the tobacco industry from successfully blocking policy initiatives: a growing political imperative, and an active and sophisticated tobacco control movement. Political will to promote public health and a strong tobacco control advocacy presence can enable governments to resist the enormous pressure exerted upon them by multinational tobacco companies.